Light Affects Host‐Symbiont Dynamics in the Non‐Photosynthetic Social Amoeba Symbiosis - Yuehui Tian; Lin Zhang; Zihe Wang; Zhili He; Longfei Shu (Ecology and Evolution)
ABSTRACT Light significantly influences phototactic behaviors and host‐bacterial interactions of photosynthetic microorganisms such as algae. The non‐photosynthetic slime mound amoeba Dictyostelium discoideum as the host shows phototaxis in the multicellular slugs, but the impact of light on amoeba‐bacteria interactions remains unclear. Here we utilized two different clades of symbiotic Paraburkholderia species, namely Paraburkholderia agricolaris B1QS70 and Paraburkholderia hayleyella B2QS11, to investigate the light‐induced symbiosis between the host amoebae and symbiotic bacteria. Our findings propose two light‐induced symbiotic types (type I and type II termed from this study) likely due to amoebae metabolites or bacterial infection efficiency. The type I symbiosis reveals increased symbiotic B1QS70 amount in amoebae QS9 under light, while stable amounts persist in amoebae QS11 and QS70, both of which are native hosts of symbiotic Paraburkholderia species. Furthermore, the transcriptomics analysis suggests that certain upregulated genes, such as lectin genes, may play crucial roles in inducing the symbiosis of P. agricolaris B1QS70 in amoebae QS9 and QS70 under light stimulation. Conversely, the type II symbiosis enhances interactions between P. hayleyella B2QS11 and three individual amoebae clones (QS9, QS11, or QS70) in dark conditions due to the strong infection capability and high growth rates of B2QS11. Transcriptomic data show that a cluster of heat shock genes is upregulated in amoebae QS9 with B2QS11 under dark, indicating an immune response to the non‐native host QS9, rather than that of in QS11 as the native host of B2QS11. Blue‐light sensors like Cryptochrome/DNA photolyase in Paraburkholderia species might regulate the growth rate by light stimulation. These findings highlight light‐regulated symbiosis between amoebae and two distinct Paraburkholderia species, indicating that light may be crucial for regulating amoebae‐symbionts dynamics.